Sustainability Assessment Methods In Oil Shale Mine Closure (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The post mining processes impacts on the environment, economy and people, whilst there may be positive contributions to the economy and social progress through mining there may also are negative impacts to the environment. The aim of this study is to elaborate sustainability assessment methodologies suitable for mine closure life cycle stage which allows defining hazardous influences on environment, society and economic dimensions, and helps quickly, conveniently and qualitatively solve, operate, find optimum variants for existing problems. The sustainability assessment methods will provides best decisions on the technological and post technological processes of a mining industry and can be used in the exploration, planning, exploitation and closure stages.